Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 9 - Roots and Radicals - Chapter 9 Test - Page 431: 7


$-12\sqrt[3] 2$

Work Step by Step

We will simplify the radical to simplify the expression: $-4\sqrt[3] {54}$ =$-4\sqrt[3] {27\times2}$ =$-4(\sqrt[3] {27}\times\sqrt[3] 2)$ =$-4(\sqrt[3] {3^{3}}\times\sqrt[3] 2)$ =$-4(3\times\sqrt[3] 2)$ =$-12\times\sqrt[3] 2$ =$-12\sqrt[3] 2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.